La tasa preferencial del impuesto a las ventas del arroz pilado y su incidencia en la comercialización del arroz pilado en el Valle Jequetepeque - Guadalupe - Vásquez Paredes, Hugo César (2017)
ABSTRACT Taxes are part of the economic life of all modern societies. Not surprisingly, the attention they have gained in economic theory. The analyzes range from general issues such as the impact of taxation on economic efficiency and general welfare, as well as other much more specific aspects that make the various tax effects with different characteristics. In the present investigation, the incidence of the Preference Tax for Sales of Pilado Rice (IVAP) in the Marketing of Pilado Rice in the Jequetepeque-Guadalupe Valley was studied, observed and concluded, for which we will study its impact within The economy of the Jequetepeque Valley. In the development of the same, the main protagonists of the IVAP were surveyed, in order to get a closer look at the process of marketing paddy rice as pounded, conception of the tax, tax declaration and payment of the same. In this thesis the basic-descriptive design was applied to narrate each of the stages in the construction of this thesis, starting with the approach of the problem, going through the confirmation of the hypothesis, until reaching the conclusion and recommendations that we can address, In order to increase the knowledge about the subject studied. After discussing the results, we conclude that the non-applicability of the preferential rate of 4% of the Sales Tax on Pilfered Rice - IVAP, and in its replacement, the application of the rate of 18 % Of the General Sales Tax, cumulative multi-phase, with the right to use the tax credit. It is recommended, directly, under the results obtained, the annulability of the preferential rate of the sales tax of the pounded rice (4%) and in its replacement return to the general sales tax rate (18%), being able to At all stages of application, deduct the tax credit for the costs and expenses that those involved in the chain may incur.